Effects of Cation Vacancies in the Phonon Raman Spectra of LaMnO3 - Granado, E. (2000)
Raman spectra of La1–xMn1–xO3 (x = 0, 0.01, 0.017, 0.022, and 0.035) and La0.91–δMn1–δO3 polycrystalline samples, taken at T = 10 K and room temperature, are presented. All La1–xMn1–xO3 samples show at T = 10 K the presence of modes at about 480 and 610 cm–1, including the rhombohedral and quasi‐cubic orthorhombic samples. However, the Raman spectrum of the rhombohedral La0.91–δMn1–δO3 sample does not show these modes at T = 10 K, but presents weak and broad structures at T = 295 K. These results are discussed in terms of local structural distortions associated with Mn vacancies and/or carrier localization in manganese perovskites.